Taxation in the Modern Economy: An In-Depth Analysis of Policy Frameworks, Economic Implications, and Strategic Approaches for Sustainable Financial Development - Caroline Caroline; Siti Sumiati; Ahmad Rizani; Loso Judijanto; Novianty Djafri (Adisam Publisher, 2024)
This paper delves into the pivotal role of taxation in shaping the intricate dynamics of the contemporary economic landscape. Focusing on the imperative of sustaining financial development, the analysis emphasizes the importance of effective tax policies. The study thoroughly examines diverse tax policies, unraveling their multifaceted dimensions and scrutinizing their direct and indirect impact on economic agents, wealth distribution, and overarching financial stability. In the pursuit of equitable growth, the analysis navigates through the complexities of various taxation strategies, assessing their potential to bridge socioeconomic gaps. The study actively engages with the challenges presented by modern taxation systems and identifies opportunities for refinement and innovation. The paper considers global economic dynamics that influence and shape contemporary tax structures in a world characterized by evolving economic paradigms. Real-world case studies are integrated, providing practical insights into the application and consequences of different tax policies. Drawing on economic theory, rigorous policy analysis, and empirical observations, the paper seeks to contribute substantially to the ongoing discourse on designing and implementing effective tax systems. By synthesizing insights from diverse perspectives, the objective is to provide a holistic understanding of taxation's pivotal role in fostering economic prosperity. In this comprehensive exploration, the paper aims to deepen scholarly understanding and offer valuable insights for policymakers, economists, and practitioners grappling with the complexities of taxation in the modern era.